Learning about solar energy - AIMS Multimedia (Chatsworth, CA : AIMS Multimedia, 1997)
Develop basic concepts about fundamental subjects includes air, light, liquids, solids and gases, solar energy sound and water
Installation guide : Macintosh, drag folder to hard drive, the double click on the program icon, Windows, run'INSTALLE.EXE' from the cd-rom, then double click the program icon
Title from disc label
Keywords: Solar energy -- Juvenile literature; Energy resources -- Juvenile literature